Perceived Usefulness and Perceived Ease of Use Influencing Intention to Use Smart Shopping Carts among Retail Customers in Malaysia - Riduan, Fatin Nur Raihana; Yusoff, Mohd Zarir (Research in Management of Technology and Business, 2026)
The rapid advancement of digital technologies has significantly transformed the retail landscape, with innovations such as smart shopping carts enhancing customer experiences through features like AI personalization, IoT inventory management, AR, and robotics. Despite these potential benefits, adoption in Malaysia remains limited due to barriers such as technology anxiety, perceived difficulty of use, and doubts about usefulness caused by technical issues such as inaccurate scanning, limited capacity, and irrelevant AI recommendations. This study aims to identify the level of factors influencing the intention to use smart shopping carts among Malaysian retail customers by determining the levels of perceived usefulness and perceived ease of use, and evaluating the relationship between these factors and customers’ intention to adopt the technology. The study employed the Technology Acceptance Model (TAM) that focuses on perceived usefulness and perceived ease of use as primary determinants. This study's target population is Malaysian retail customers aged 18 and above, who have purchasing power. Data were collected through an online questionnaire distributed via Google Forms, resulting in 273 valid responses from a sample size of 384 that was determined using Krejcie & Morgan’s (1970) table. Data analysis was conducted using SPSS, including descriptive statistics, reliability testing, normality checks, and Spearman’s correlation analysis. The results indicate high levels of perceived usefulness, perceived ease of use, and intention to use smart shopping carts, with strong positive correlations between perceived usefulness and intention to use (r = 0.767, p < 0.01) and between perceived ease of use and intention to use (r = 0.735, p < 0.01). Perceived usefulness and perceived ease of use are considered sufficient in this study because they capture customers’ primary evaluations of whether the smart shopping cart provides clear benefits and whether it can be used without difficulty. Therefore, this study focuses on PU and PEOU as the core predictors of intention to use smart shopping carts. Future research is recommended to explore additional factors and utilize mixed methods to gain deeper insights into smart shopping cart usage in